A General Synthesis of Mesoporous Hollow Carbon Spheres with Extraordinary Sodium Storage Kinetics by Engineering Solvation Structure. Issue 10 (19th December 2021) - Chen, Yang; Zhao, Si; Yu, Yueyue; Wei, Mingdeng; Mathur, Sanjay; Hong, Zhensheng
Abstract: Porous and hollow carbon materials have great superiority and prospects in electrochemical energy applications, especially for surface charge storage due to the high active surface. Herein, a general strategy is developed to synthesize mesoporous hollow carbon spheres (MHCS) with controllable texture and compositions by the synergistic effect of dopamine polymerization and metal catalysis (Cu, Bi, Zn). Mesoporous MHCS–Cu and MHCS–Bi are regular spheres, while mesoporous MHCS–Zn possesses an inward concave texture, and simultaneously has a very high surface area of 1675.5 m 2 g ‐1 and lower oxygen content through the catalytic deoxygenation effect. MHCS–Zn displays an exceptional sodium storage kinetics and excellent long cycling life with 171.9 mAh g ‐1 after 2500 cycles at 5 A g ‐1 in compatible ether‐based electrolytes. Such electrolyte enables enhanced solvated Na + transport kinetics with appropriate electrostatic interactions at the surface of carbon anode as revealed by molecular dynamics simulations and molecular surface electrostatic potential calculations. Such an anode also displays basically constant capacity working at 0 °C, and still delivers 140 mAh g ‐1 at 3 A g ‐1 under ‐20 °C. Moreover, MHCS–Zn anode is coupled with Na3 V2 (PO4 )3 cathode to construct a hybrid capacitor, which exhibits a high energy density of 145 Wh Kg ‐1 at a very high power of 8009 W kg ‐1 . Abstract : A general strategy is reported to synthesize mesoporous hollow carbon spheres (MHCS) with controllable morphology and compositions by the synergistic effect of dopamine polymerization and metal catalysis. MHCS‐Zn simultaneously possesses a very high surface area and low oxygen content, enabling ultrafast Na‐ion storage in a compactable electrolyte toward a high energy and power density hybrid capacitor.